Outcome of Delayed Lacrimal Probing in Congenital Obstruction of Nasolacrimal Duct - Muhammad Moin, Rao Muhammad Rashad Qamar, Ejaz Latif, Muhammad Younis Tahir (Pakistan Journal of Ophthalmology, 2011)
Purpose: This study was conducted to evaluate the success of probing in congenital nasolacrimal duct obstruction in children age 13 months and older and to establish factors predictive of the outcome Material and Methods: It was a single center, prospective, interventional case series. The study was carried out from April 2007 to October 2009. The study was conducted at the Department of Ophthalmology, Bahawal Victoria Hospital, Bahawalpur. We treated 110 eyes of 100 patients selected by universal sampling technique. Diagnosed cases of nasolacrimal duct blockade of any age and either sex were included. No patient with epiphora due to congenital nasolacrimal duct blockade was excluded. After securing complete aseptic measures each punctum was dilated one after the other, using Bowman’s probes under general anesthesia. Data was collected on special proforma and analyzed with the help of SPSS. Results: The study population comprised of 110 blocked nasolacrimal ducts of one hundred (100) patients. Male to female ratio was 2:3. All the bilateral cases were females. Age ranged between 13-32 months (Mean = 17 months). About 2/3rd patients were between 13 and 24 months. All patients had epiphora since birth. One attempt at probing resulted in resolution in 84.54 % (93 of 110) eyes. 17 eyes (15.45%) needed a repeat procedure. The overall success rate was 92.72% (102 of 110) and 08 cases resulted in failures. 04 were bilateral (all were females) and 04 were unilateral (02 males and 2 females). There was no significant difference in the cure rate with increasing age (P = 0.60). Complications were noted in none of the patients. Conclusions: Results indicate that probing is a viable primar